Associations between traumatic stress symptoms, pain and bio-active components in burn wounds. (October 2018) - Van Loey, N.E.; Hofland, H.W.C.; Vlig, M.; Vandermeulen, E.; Rose, T.; Beelen, R.H.J.; Ulrich, M.M.W.
Highlights: Lower oxytocin levels in the wound were associated with higher acute traumatic stress levels. Lower oxytocin levels in the wound were associated with higher pain scores. Traumatic stress may influence pain in the wound through a hormonal pathway. Abstract: Objective: Pain and traumatic stress symptoms often co-occur. Evidence suggests that the neuropeptide oxytocine and pro-inflammatory cytokines are associated with both stress and pain. The aim of this pilot study was to explore relations between self-reported pain and traumatic stress, oxytocin and three cytokines in burn wounds. Methods: An observational study in three burn centres was performed. Patients were invited to participate in the study when deep dermal injury was suspected. Patients completed the Impact of Event Scale (IES), a self-report questionnaire assessing traumatic stress symptoms, and they rated their pain the day prior to surgery. During surgery, eschar (i.e., burned tissue) was collected and stored at −80 ° C until analysis. When the data collection was complete, oxytocin and cytokine levels were analysed. Results: Eschar from 53 patients was collected. Pain and stress scores were available from 42 and 36 patients respectively. Spearman correlational analyses showed an association between lower oxytocin levels at wound site and a higher total IES score (r = −0.37) and pain (r = −0.32). Mann-Whitney U tests comparing groups scoring high or low on pain or stress confirmed these associations. Conclusion: These analyses lend support to a hormonal pathway that may explain how psychological distress affects pain at skin level in patients with traumatic stress symptoms.